Implementation of Etlingera Elatior for Unique Branding of Central Sulawesi Batik Motif - Ikram; Abdi; Mutmainna, Nurul; Khasmawati, Julia; Wahyuli, Diana; Sudarsana, I Wayan; Junaidi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2022)
Batik is the art work of the Indonesian people which is a cultural heritage from their ancestors which has become one of the world's recognized cultural heritages. Batik itself has a variety of patterns that are influenced by the customs of the local community and contains deep meaning and philosophy. Endemic flora and fauna are often used as patterns for batik motifs. In the process of forming batik motifs, mathematical knowledge is often required which sometimes appears naturally. Mathematics that is closely related to culture is called ethnomathematics as a branch of mathematics. Ethnomathematics can be used in forming batik patterns, especially fractal forms. A fractal shape is an object that appears to have a symmetric self-resemblance to one another when viewed at a certain scale and is the smallest part of the overall structure of the object. The purpose of this research is to make fractals of local batik motifs from Central Sulawesi using the endemic plant of Bunga Katimong (Etlingera Elatior) with the help of the j-Batik application so that new motifs are obtained to add to the diversity of existing batik motifs. The new batik motifs produced in this research are Katimong, Kantan, Kincung and Honje.